2014
DOI: 10.1111/sdi.12185
|View full text |Cite
|
Sign up to set email alerts
|

Fistula Eligibility: A Work in Progress

Abstract: Effective hemodialysis requires a reliable vascular access. Clinical practice guidelines strongly recommend the fistula as the preferred option followed by arteriovenous (AV) grafts, with central venous catheters being least preferred. Recently, there has been a growing awareness of the limitations of the fistula, its high rate of primary failure and that a fistula may not be appropriate for all patients initiating or on hemodialysis. However, determinates for fistula eligibility have not been clearly defined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
(81 reference statements)
0
6
0
Order By: Relevance
“…Although grafts require more procedures to maintain patency, fistulas require more procedures to establish patency, with the result that overall patency may not differ substantially between the two forms of permanent access [36]. Due to the high primary failure rate and need for multiple procedures to maintain patency with a poor patient quality of life, the eligibility in elderly patients should be carefully determined [37, 38]. However, in skilled hands the endovascular treatment of AVF complications appears to be a valuable approach even in nonagenarians in view of its low invasiveness, low complication rate, and relatively good long-term patency rate [39].…”
Section: Va In Elderly Patients: Recent Findingsmentioning
confidence: 99%
“…Although grafts require more procedures to maintain patency, fistulas require more procedures to establish patency, with the result that overall patency may not differ substantially between the two forms of permanent access [36]. Due to the high primary failure rate and need for multiple procedures to maintain patency with a poor patient quality of life, the eligibility in elderly patients should be carefully determined [37, 38]. However, in skilled hands the endovascular treatment of AVF complications appears to be a valuable approach even in nonagenarians in view of its low invasiveness, low complication rate, and relatively good long-term patency rate [39].…”
Section: Va In Elderly Patients: Recent Findingsmentioning
confidence: 99%
“…Optimizing VA outcomes requires an appropriate choice of VA type and surgical strategy, on the basis of patient's characteristics and anatomy of vessels [32,33] . Substantial comorbidities, older age and female gender are 118 recognized risk factors of primary fistula failure [11,12,15,18] .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the primary failure rate is two times greater for fistulas (40%) than AVG (19%), with similar cumulative patency, in addition, the number of catheter days before AV access use was more than double in those having a fistula (81 days) compared with AVGs (38 days). However, grafts require more angioplasties (1.4 vs. 3.2 events) and thrombolysis (0.05 vs. 0.98 events) interventions per 1000 patient-days [76,77]. The risk of primary fistula failure is much higher for lower arm fistula (28%) than with upper arm fistula (20%) [75].…”
Section: Vascular Access Choice: Selection Biasmentioning
confidence: 99%